The distribution of total work in the EU and US - Michael C. Burda; Daniel S. Hamermesh; Philippe Weil (Institute for the Study of Labor (IZA), 2006)
Using two time-diary data sets each for Germany, Italy the Netherlands and the U.S. from 1985-2003, we demonstrate that Americans work more than Europeans: 1) in the market; 2) in total (market and home production) - there is no one-for-one tradeoff across countries in total work; 3) at unusual times of the day and on weekends. In addition, gender differences in total work within a given country are significantly smaller than variation across countries and time. We conclude that some of the transatlantic differences could reflect inferior equilibria that are generated by social norms and externalities. While an important outlet for total work, home production by females appears very sensitive to tax rates in the G-7 countries. We adapt the theory of home production to account for fixed costs of market work and adduce evidence that they, in contrast to other relative costs, vary significantly across countries.
Keywords: J22; E24; D13; 330; time use; gender inequality; household production; hours of work